Transforming Peperomia pellucida into a Modern Pharmaceutical Tablet for Gout - Eva Chiara Zittelli; Prudente Estabaya Pabayo; Maria Eva Julieta; Thanarat Chakthranont; Busarakorn Pongkarn (Journal of Advances in Medicine and Pharmaceutical Sciences, 2025)
Ulasimang Bato is a plant endemic to the Philippines, which is known in Latin as Peperomia pellucida. Ulasimang Bato has been widely used in the Philippines as a conventional treatment for gout. This study sought to assess the conversion of Ulasimang Bato into a contemporary pharmaceutical tablet for the treatment of gout, by examining its efficacy, safety, and use in the formal health care system alongside Allopurinol, a conventional therapy. The study was conducted from February to April 2025, a clinical trial was conducted with 300 participants, consisting of 150 people taking Ulasimang Bato tablets and 150 people taking Allopurinol, from rural areas of the Philippines. Laboratory tests validated the presence of active constituents, including flavonoids, tannins, and phenolic acids, which are thought to play a role in the anti-inflammatory, analgesic, and antioxidant properties. The study revealed that Ulasimang Bato tablets offered similar symptom relief to Allopurinol, with significantly fewer side effects, especially those related to gastrointestinal problems. This suggests that Ulasimang Bato could be a safer option for gout sufferers, especially those who cannot tolerate the side effects of Allopurinol. Furthermore, the integration of traditional medicine into the formal healthcare system shows significant community acceptance, although there are still obstacles in terms of regulation and training for healthcare practitioners. Future research should focus on extensive clinical trials to ensure the long-term safety and efficacy of Ulasimang Bato, while addressing the obstacles to its integration into the healthcare system.